دراسة وتحليل أثر النفقات العامة على النمو الاقتصادي دراسة حالة الجزائر 1980-2018 - عبد الحميد, زنينة; محمد ياسين, بوغزالة محمد (University of eloued جامعة الوادي, 2020)
"استهدفت الدراسة البحث في العلاقة بين الإنفاق العام والنمو الاقتصادي في الاقتصاد الجزائري خلال الفترة (1980-2018)، ولبيان فيما إذا كانت السلاسل الزمنية للمتغيرين مستقرة من عدمها، تطلب استخدام بعض الأدوات الإحصائية، إضافة إلى اختبارات جذر الوحدة، كما تم تحديد رتبة تكامل كل متغير حدة. وتبين أن المتغيرات متكاملة من الدرجة الأولی، وفي ضوء ذلك، تم استخدام اختبار التكامل على المشترك لكل من طريقة انجل - جرانجر وطريقة جوهانسن، بالإضافة إلى استخدامنا لمنهجية جرانجر للسببية، وذلك للتحقق من وجود علاقة طويلة الأمد بينهما .واتضح من خلال التحليل عدم وجود علاقة سببية بين الإنفاق العام والنمو في الاقتصاد الجزائري خلال الفترة المعنية بالدراسة. وكان التفسير المحتمل لذلك يرجع إلى طبيعة الاقتصاد الوطني الذي يعتمد بشدة على قطاع المحروقات كمصدر رئيسي للدخل الوطني، وعدم تنوع النشاط الاقتصادي وهيكل الصادرات من جهة، وإلى ضعف الطاقة الاستيعابية للاقتصاد الوطني من جهة أخرى. "The study aimed to examine the relationship between public spending and economic growth in the Algerian economy during the period 1990-2016. To determine whether the time series of the variables are stable or not, some statistical tools are required, in addition to unit root tests, and the rank of integration of each variable is determined separately. It was found that the variables were first-order integrators. In this light, the combined integration test of the Engel-Granger method and the Johansen method was used, in addition to our use of the Granger's causality methodology, to verify a long-term relationship between them. The analysis showed that there was no causal relationship between public expenditure and growth in the Algerian economy during the study period. The probable explanation for this was the nature of the national economy, which relied heavily on the hydrocarbon sector as a major source of national income, the lack of diversification of economic activity and the structure of exports, and the weak absorptive capacity of the national economy. Keywords: public expenditure, economic growth, Algerian economy, synchronous integration, causation Granger, Error correction model.
مذكرة ماستر اقتصاد كمي
Keywords: الإنفاق العام، النمو الاقتصادي، اقتصاد جزائري، تكامل متزامن، سببية جرانجر، نموذج تصحيح الخطأ; public expenditure, economic growth, Algerian economy, synchronous integration, causation Granger, Error correction model